Financial and Technical Assistance in the Reconstruction and Development of Post-Conflict Bosnia and Herzegovina - Goran Nedic (The Vienna Institute for International Economic Studies (wiiw), 2006)
Ineffective aid management and coordination as well as old fashion model of aid sequencing were few of the major culprits why Bosnia and Herzegovina is still not on self sustainable path. Government representatives should eagerly embrace newest incentive related to increase in aid effectiveness-Paris Declaration. Commitments of Official Development Assistance in Bosnia and Herzegovina exceeded 7 billion from 1996 to 2004. We presented sectoral destination of aid funds and indicators of aid effectiveness. While aid driven post-conflict reconstruction has been relatively successful, insufficient structural reforms made BiH lagging behind most of the transition countries in the region. The most important achievements took place in the peace implementation activities which were necessary for ensuring reconciliation and a fertile ground for reconstruction and recovery. International support for establishment and maintenance of security exceeded 18 billion in the period 1996-2004. Further reforms, expected in near future, would not be possible in politically essentially divided country without promised the pot of gold that was held to come with EU membership.
Keywords: 330